PENGARUH KUALITAS PRODUK, HARGA, DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONEOPPO DI KELURAHAN PASIR PUTIH - Nada Nurmaya, - (2019)
This study is a quantitative study aims to know the effect of the quality product, the price, and advertisement toward buying decision. The population of this study is the society of district Pasir Putih, Depok. The sample was conducted for 75 respondents. The methodology of this study is non-probability sampling,especially purposive sampling. The data was collected by distributing the questionnaire. This study analyzed using PLS (Partial Least Square) analysis technique. The result of this study showed that (1) the product quality significantly affect the buying decision with the coefficient percentage as big as 0,159. (2) the price did not significantly affect the buying decision with the coefficient percentage as big as -0,073. (3) the advertisement significantly affect the buying decision with the coefficient as big as 0,497.